2013
DOI: 10.4236/aa.2013.32015
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Biomarkers into Research with Latino Immigrants in the United States

Abstract: Despite extensive research into the toll of persistent psychosocial stress on individual physiology and health, little is known about the effects of chronic biosocial stress for immigrant populations. In the present paper, the authors review challenges encountered when integrating minimally-invasive stress-related biomarkers (e.g., blood pressure, Epstein-Barr Virus [EBV] antibodies, C-reactive protein [CRP], and salivary cortisol), as well as anthropometric (e.g., height, weight, waist circumference) and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…These results are consistent with previous studies that the implementation of culture-specific strategies successfully leads to the recruitment and retention of Latinos (Cabral Haack et al 2014;Kao et al 2011;McClure et al 2013). Furthermore, these findings are consistent with previous findings indicating that minority families are as willing as majority ethnic groups to participate in research once they have been invited and have access to the study information in a language they understand (Wendler et al 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous studies that the implementation of culture-specific strategies successfully leads to the recruitment and retention of Latinos (Cabral Haack et al 2014;Kao et al 2011;McClure et al 2013). Furthermore, these findings are consistent with previous findings indicating that minority families are as willing as majority ethnic groups to participate in research once they have been invited and have access to the study information in a language they understand (Wendler et al 2005).…”
Section: Discussionsupporting
confidence: 92%
“…A study of women involved in cancer research found that outreach to potential participants who were low-income and/or members of ethnic minority groups were less effective when using traditional recruitment efforts which were found effective for members of majority populations of higher socioeconomic status (Brown et al 2000). Similarly, behavioral health and health research has identified other culturally sensitive strategies at the participant level that contribute to successful recruitment and retention of Latino participants, including: (1) partnering with community agencies, (2) reassuring families that information will be kept confidential, (3) ongoing (face to face) contact with families, (4) arranging child care and transportation to minimize barriers, (5) providing information about the study in Spanish, (6) recruiting bilingual research staff, (7) providing follow up support and access to additional services, and (8) providing a flexible schedule (Cabral et al 2003;McClure et al 2013;Haack et al 2014). The importance of face-toface contact at the outset has been reinforced in some studies that report their study outreach staff members were able to overcome some of the barriers to recruitment of populations underrepresented in research reported in the literature (Cabral et al 2003;Kao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers argue that emotional stress may help explain health disparities patterned across lines of race and socio-economic status. A small but promising body of literature has begun to use bio-marker data to link migration-related stressors to physical health declines ( 57 59 ). Says Sternberg: “we are discovering that while feelings don’t directly cause or cure disease, the biological mechanisms underlying them may cause or contribute to disease” (2001: 13).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological measures can be used as proxies or outcomes of psychological phenomenon. Examples of work utilizing physiological biomarkers in anthropology include: cortisol measures for indexing psychosocial stress (McClure et al 2013), elevated blood pressure correlating with an individual's level of "cultural consonance" (Dressler and Bindon 2000;Dressler et al 1987), and relocation-induced stress impacting telomere length (Zahran et al 2015). These are all observations on a longer timescale.…”
Section: The Ecocultural Environment Individual Youth and Electrodementioning
confidence: 99%